2005
DOI: 10.1175/mwr2906.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Bayesian Model Averaging to Calibrate Forecast Ensembles

Abstract: Ensembles used for probabilistic weather forecasting often exhibit a spread-error correlation, but they tend to be underdispersive. This paper proposes a statistical method for postprocessing ensembles based on Bayesian model averaging (BMA), which is a standard method for combining predictive distributions from different sources. The BMA predictive probability density function (PDF) of any quantity of interest is a weighted average of PDFs centered on the individual bias-corrected forecasts, where the weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
1,477
1
25

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,587 publications
(1,516 citation statements)
references
References 44 publications
13
1,477
1
25
Order By: Relevance
“…The simplest ensemble approach (simple arithmetical averaging) and an advanced ensemble approach (BMA) were both used in this study. Raftery et al (2005) proposed a BMA approach which involves statistical post-processing to produce calibrated and sharply predictive PDFs from ensembles of dynamic models, and provide a reliable description of the total modeling uncertainty. The BMA predictive PDF is a weighted average of PDFs centered on the bias-corrected forecasts from a set of individual ensemble members, based on measures of their probabilities, with the better-performing ensemble members being assigned a higher weighting than those that produced less satisfactory results:…”
Section: Ensemble Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest ensemble approach (simple arithmetical averaging) and an advanced ensemble approach (BMA) were both used in this study. Raftery et al (2005) proposed a BMA approach which involves statistical post-processing to produce calibrated and sharply predictive PDFs from ensembles of dynamic models, and provide a reliable description of the total modeling uncertainty. The BMA predictive PDF is a weighted average of PDFs centered on the bias-corrected forecasts from a set of individual ensemble members, based on measures of their probabilities, with the better-performing ensemble members being assigned a higher weighting than those that produced less satisfactory results:…”
Section: Ensemble Approachmentioning
confidence: 99%
“…(9), we obtain the posterior predictive PDF of the predictive variable, such as soil moisture in this study. In the original BMA approach, Raftery et al (2005) assumed that the conditional PDF was Gaussian, but the probability distribution of soil-moisture error is nonGaussian. Tian et al (2011) found that the gamma distribution gives a better approximation of the soil-moisture error than the Gaussian distribution.…”
Section: Ensemble Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with the model differences, many multi-model ensemble approaches have emerged, including Bayesian Model Averaging (BMA) methods proposed by Raftery et al (2005) and superensemble approach (Krishnamurti et al, 1999), which strive to obtain consensus model predictions by weighing model predictions based on their consistency with observations. Ensemble forecasting approach has not only been used to develop multi-model predictions, it is also a popular approach in treating uncertainties from different sources, including model inputs, ICs, and model parameters.…”
Section: Uncertainties In Hydrological Forecastingmentioning
confidence: 99%
“…The need for accounting for model structure uncertainty by multi-model averaging have motivated researchers in various fields such as economic, weather and hydrological forecasting to consider multi-model methods that aim to obtain consensus prediction from a set of models by different averaging schemes (Bates and Granger 1969;Dickinson 1973;Krishnamurti et al 1999;Shamseldin et al 1997;Stockdale 2000;Raftery et al 2005). One way to aggregate multiple deterministic model outputs is to employ deterministic techniques (i.e.…”
Section: Introductionmentioning
confidence: 99%